The impacts of ERP systems on public sector organizations - Fernandez, Dahlia; Zainol, Zaini; Ahmad @ Abdul Mutalib, Hawa (Elsevier, 2017)
The aim of this study is to investigate the impact of Enterprise Resource Planning (ERP) system on Public Sector Organizations (PSO) using two perspectives of the Balanced Scorecard (BSC) performance measurement framework; financial and customer. This study presents evidence based on questionnaires survey conducted with 52 local authorities in Malaysia which have implemented the system. Empirical evidence shows that the uses of ERP system in PSOs resulted in a positive financial performance and provide better services to the customer. The corresponding results from the survey signaling to the needs of an integrated system such as ERP to be implemented by other PSOs to enhance the financial and customer performance.